MENINGKATKAN DISIPLIN BELAJAR SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PPKn KELAS VIII MTs AL WASHLIYAH KOLAM - Setiawan Setiawan; Ulian Barus (STKIP Subang, 2024)
This Research aims to improve student learning discipline by applying the Problem based Learning model to the class VIII Civics subject at MTs Al washliyah Kolam.This tipes of research is class room action research carried out in 2 cycles.The research instruments are observation sheets and test. The data obtained was analyzed using quantitative analysis to calculate the percentage increase.based on data analysis, it turn out that students Civics experiences an increase in learning discipline every cycle. The average increase in student learning discipline from cycle I to cycle IIincreased, in cycle I the average learning disciplinr test was 65,59% and in cycle II the average learning discipline test was 77,35%. The increase in Civics learning discipline in cyle I was 25,53%, then uncreased in cycle II to 75,53%. The conclucion of this reasearsch is that the Problem Based Learning model can improve the learning discipline of class VIII student at MTs Al Washliyah Kolam